A reconfiguração da experiência de ser doméstica através da página “Eu empregada doméstica” - Enise de Castro Silva (2019)
This dissertation investigates what the reports on the Facebook page “Eu empregada doméstica” say about women’s living as domestic employees and how they contribute to a reconfiguration of the experience of being domestic in the Brazilian contemporary context. In order to do so, posts from the first three months of page activity, from June 19th of 2016 to September 19th of 2016, were analyzed. This period has been selected due to the great traffic after the action of the page’s creator, Joyce Fernandes, went viral. To analyze the material, we started from John Dewey's perspective on experience together with studies that talk about the relation between subject and work and domestic employment in Brazil. It also required a reflection on the role that giving account of oneself exercises in that context and how representations of being domestic employees are created starting from the page reports. In the first moment, we analyzed the content of the posts and classified them in six groups according to the women’s definition of the situations: deprivation of basic conditions, ethical-moral degeneration, racism and xenophobia, physical and sexual violence, positive and grateful accounts and reports by Joyce. Within the largest groups of reports, we have done a second content analysis, refining the characterization of the situation. Thus, we were able to interpret that the representations of domestic work present on the page are linked to Brazilian’s social, racial and gender inequalities and are also linked to a capitalist and Western civilization’s comprehension of work.